Sustainability and Immateriality - Motivations of users/consumers as drivers of sustainability (2019)
At present, it is necessary to analyse how users/consumers perceive sustainability, in order to determine the characteristics, aspects, attributes, etc. that, according to their criteria, must have sustainable products, services and product-service systems (hereinafter SPS). The purpose of this study is to analyse, from the point of view of some experts, whether the proposed motivations of users/consumers are related to sustainability; since it is considered that the study of collective actions from the emotions can become a conscious motivating motor that would have the purpose of transforming a reality, in this case, the relation between users/consumers and sustainability. The analysis is the result of previous research (Rivera et al, 2015; Rivera & Hernándis, 2016; and Rivera-Pedroza ,2017), to investigate how diverse motivations and aspirations, which are not only basic needs, could be related to sustainability. The research is carried out based on an instrument which contains eleven drivers linked to motivations (needs, emotions, values) belonging to an immaterial context of sustainability in products/services. The analysis of these motivations, within the current context, provides value in the analysis of the behaviours of people involved in the environmental social movements within the emerging design and sustainability scenarios. © 2019 Universidade do Vale do Rio dos Sinos. All rights reserved.